Characterization of Burkholderia pseudomallei isolated in Thailand and Malaysia - Radua, Son; Ling, Ooi Wai; Srimontree, Siripen; Lulitanond, Aroonluk; Hin, Wong Foo; ., Yuherman; Lihan, Samuel; Rusul, Gulam; Mutalib, Abdul Rahim (2000)
A total of 35 Burkholderia pseudomallei isolates from Thailand (16 clinical and eight soil isolates) and Malaysia (seven animal, two isolate each from clinical and soil) were investigated by their antimicrobial resistance, plasmid profiles and were typed by randomly amplified polymorphic DNA analysis. All isolates were found to be resistant to six or more of the 12 antimicrobial agents tested. Only two small plasmids of 1.8 and 2.4 megadalton were detected in two clinical isolates from Thailand. RAPD analysis with primer GEN2-60-09 resulted in the identification of 35 RAPD-types among the 35 isolates. The constructed dendrogram differentiated the 35 isolates into two main clusters and a single isolate. The wide genetic biodiversity among the 35 isolates indicate that RAPD-PCR can be a useful method to differentiate unrelated B. pseudomallei in epidemiological investigation. (C) 2000 Elsevier Science Inc.